Parent-child career goal congruence and career optimism in relation to career engagement among university students - Pristyani Meylinda; Arini Widyowati (Universitas Mercu Buana Yogyakarta, 2025)
This study aimed to investigate the association between parent-child career goal congruence, career optimism, and career engagement among students. This study involved 237 students aged 19 to 21 years (M-age = 19.23; SD = 0.97), with 82.3% female and 17.7% male participants, drawn from a faculty at a university in Yogyakarta, Indonesia. The research employed a quantitative design using a survey method. Data was collected using three scales: the parent-child career goal congruence scale (α = 0.87), the career optimism scale (α = 0.81), and the career engagement scale (α = 0.86). Multiple linear regression analysis (SPSS 27.0) revealed that parent child career goal congruence and career optimism were associated with career engagement (R = 0.39, R2 = 0.16, F = 22.08, p < 0.001). Together, these two factors account for 16% of the variance in career engagement. However, when examined separately, only parent-child career goal congruence was associated with career engagement (β = 0.21, p < 0.001), while career optimism showed no significant association (β = 0.03, p = 0.38). This finding highlight the value of collaborative, communication-centered approaches, suggesting that parents and career counselors can support students more effectively by engaging in joint career planning, open dialogue, and structured counseling sessions to enhance parent–child career goal congruence. Keyword: Parent-child career goal congruence, career optimism, career engagement.